Application of TPACK Learning For Elementary School Teachers to Improve Numeracy Literacy Skills in Sosial Subject at Lesanpuro 1 Elementary School - Surayanah, Surayanah; Rofiki, Imam; Ramila, Audiza Assyifa; Cholida, Nur; Lestariningsih, Lestariningsih; Zainuddin, M; Fikriyah, I'anah El (Journal of Development Research, 2024)
Numeracy literacy skills in Indonesia are currently still very low which has an impact on the quality of education. Overcoming this requires learning innovation, one of which is through TPACK learning. Based on the results of the needs analysis conducted at SDN Lesanpuro 1 Malang City, TPACK learning training is still needed to support teacher professionalism. The purpose of this study is to analyze how TPACK learning training at SDN Lesanpuro 1 Malang City can affect teacher competence. The research method used is training and mentoring teacher competencies through several stages, namely, planning, implementation, and evaluation. Data in the form of documentation and test results will be analyzed descriptively qualitative to describe the achievement of the program. The results of this study indicate an increase in the ability of teachers to present TPACK learning as indicated by the average score of learning implementation of 86.1. Meanwhile, in the aspect of learning evaluation, the test results were obtained with an average of 82.3 which was included in the good category.